Electric power generation from solar pond using combined thermosyphon and thermoelectric modules - Randeep Singh (2018)
Salinity-gradient solar ponds can collect and store solar heat at temperatures up to 80 °C. As a result, these water bodies act as a renewable source of low grade heat which can be utilized for heating and power generation applications. In this paper, design and test result of the combined system of thermosyphon and thermoelectric modules (TTMs) for the generation of electricity from low grade thermal sources like solar pond is discussed. In solar ponds, temperature difference in the range 40-60 °C is available between the lower convective zone (LCZ) and the upper convective zone (UCZ) which can be applied across the hot and cold surfaces of the thermoelectric modules to make it work as a power generator. The designed system utilizes gravity assisted thermosyphon to transfer heat from the hot bottom to the cold top of the solar pond. Thermoelectric cells (TECs) are attached to the top end of the thermosyphon which lies in the UCZ thereby maintaining differential temperature across them. A laboratory scale model based on the proposed combination of thermosyphon and thermoelectric cells was fabricated and tested under the temperature differences that exist in the solar ponds. Result outcomes from the TTM prototype have indicated significant prospects of such system for power generation from low grade heat sources particularly for remote area power supply. A potential advantage of such a system is its ability to continue to provide useful power output at night time or on cloudy days because of the thermal storage capability of the solar pond. © 2010 Elsevier Ltd.